Examining A Model Of Human Resource Performance In Tourism Destination After Pandemic - Dian Marlina Verawati; Andhatu Achsa; Ivo Novitaningtyas (Jurnal Manajemen, 2022)
During the new normal era after the pandemic of Covid-19, the tourism destination needs to struggle and adapt for recovery. This process requires optimal human resource performance. The objective of this study is to examine the model of human resource performance in tourism destination after pandemic. Leadership, motivation, and organizational commitment are considered as the antecedents of human resource performance. This study implements a quantitative approach. The data collection method used a questionnaire that was distributed to 105 employees in Balkondes as respondents. The data analysis method used Structural Equation Model (SEM) with AMOS. The results show that leadership, motivation, and organizational commitment have a positive and significant effect on human resource performance. The results also show that organizational commitment has mediating effect on the relationship between leadership toward human resource performance, and motivation toward human resource performance.